2019
DOI: 10.1002/lsm.23152
|View full text |Cite
|
Sign up to set email alerts
|

Selective Sebaceous Gland Electrothermolysis Using a Single Microneedle Radiofrequency Device for Acne Patients: A Prospective Randomized Controlled Study

Abstract: Background and Objectives The selective electrothermolysis of the sebaceous glands was suggested as a novel therapeutic option for facial acne. However, there has been no randomized controlled trial to evaluate the effectiveness and safety of the monopolar radiofrequency (RF) device using single microneedle with proximal insulation. The objective of the study was to evaluate the efficacy and tolerability of intralesional electrothermolysis using monopolar RF device and proximally‐insulated single microneedle i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…In studies that used RF for acne or scarring, lesion count and sebum were measured for objective improvement. 28,[35][36][37] Three-dimensional imaging objectified skin topography of acne scars, fat content, and aging. 18,32,[38][39][40][41][42] Ultrasound measured fat thickness and skin density.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies that used RF for acne or scarring, lesion count and sebum were measured for objective improvement. 28,[35][36][37] Three-dimensional imaging objectified skin topography of acne scars, fat content, and aging. 18,32,[38][39][40][41][42] Ultrasound measured fat thickness and skin density.…”
Section: Resultsmentioning
confidence: 99%
“…Supporting Information Data outlines the efficacy measurement tools used. In studies that used RF for acne or scarring, lesion count and sebum were measured for objective improvement 28,35–37 . Three‐dimensional imaging objectified skin topography of acne scars, fat content, and aging 18,32,38–42 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to the development of technologies with a more favorable profile, such as FRF. FRF devices have been proven to decrease the propensity for postinflammatory hyperpigmentation and the aforementioned problems of ablative lasers, all while achieving a similar level of acne scar reduction 13,27,28 . The efficacy of FRF compared to other treatment modalities for acne scarring has previously been investigated in a Cochrane review 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Various RF devices have been developed and used to treat wrinkles, acne, hyperhidrosis, etc. A recent study on treatment with RF devices for acne vulgaris, a disease in which an overactive sebaceous gland may be part of its pathogenesis, has confirmed that a micro-needling RF device can improve sebum production by decreasing the sebaceous gland [3].…”
Section: Introductionmentioning
confidence: 97%